1994
DOI: 10.1007/bf02172229
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of assessment methods for depression in mental retardation

Abstract: Investigated the association between various depression assessment methods in 38 adults with mild or moderate mental retardation, half of whom had relatively high and the other half had relatively low depression screening scores. Measures included a standard psychiatric interview (Diagnostic Interview for Children and Adolescents), an informant rating scale (Reiss Screen for Maladaptive Behavior), and a self-report measure (Self-Report Depression Questionnaire). Association between measures was generally low, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…The Schedule for Affective Disorder and Schizophrenia (SADS; Endicott & Spitzer 1978) was used without modification to diagnose schizophrenic patients with IQs between 50 and 70 (Meadows et al 1991). The Diagnostic Interview for Children and Adolescents (DICA; Herjanic & Campbell 1977) was used to assess depression in adults with ID (Rojahn et al 1994). According to Puig-Antich et al (1983), the Kiddie-SADS (K-SADS) interview can be used in children with mild ID without severe language impairment.…”
Section: Introductionmentioning
confidence: 99%
“…The Schedule for Affective Disorder and Schizophrenia (SADS; Endicott & Spitzer 1978) was used without modification to diagnose schizophrenic patients with IQs between 50 and 70 (Meadows et al 1991). The Diagnostic Interview for Children and Adolescents (DICA; Herjanic & Campbell 1977) was used to assess depression in adults with ID (Rojahn et al 1994). According to Puig-Antich et al (1983), the Kiddie-SADS (K-SADS) interview can be used in children with mild ID without severe language impairment.…”
Section: Introductionmentioning
confidence: 99%
“…Two studies comparing informant and self-report assessments of depression report contradictory results. Rojahn & Warren (1994) found no meaningful agreement between a standard psychiatric interview, an informant rating scale and a self-report rating scale. However, Gordon et al (2007) found high correlations between the self-ratings of adults with ID with ratings by their key workers on the Zung Depression Inventory.…”
Section: Introductionmentioning
confidence: 77%
“…Two studies comparing informant and self‐report assessments of depression report contradictory results. Rojahn & Warren () found no meaningful agreement between a standard psychiatric interview, an informant rating scale and a self‐report rating scale. However, Gordon et al .…”
Section: Introductionmentioning
confidence: 99%
“…Walsh & Shenouda (1999) showed that the ABC and the Adaptive Behaviour Subscale (Nihira et al 1993) predicted the RSMB total score well in a clinical sample. Rojahn & Warren (1994) found adequate test‐retest reliability, but the agreement between the two depression subscales of the RSMB, and a psychiatric interview and a self‐report measure yielded low levels of convergent validity.…”
Section: Introductionmentioning
confidence: 99%